Dynamic investigation of a hybrid suspension and cable stayed bridge. - Paultre, P.
Ambient and forced vibration tests were carried out on the Beauharnois bridge, a unique, 177-m combined suspension and cable stayed structure near Montreal, Canada. A rehabilitation program was completed on the bridge during which the deck was completely rebuilt with an orthotropic slab on two steel trusses. The rehabilitation program also included the addition of two pairs of stay cables on both towers, creating a hybrid suspension system. The paper presents a series of dynamic tests performed to evaluate the dynamic properties and the dynamic amplification factor (DAF) for the rehabilitated bridge. The experimental program involved the measurement of vertical, transverse, and longitudinal acceleration responses of the deck and tower under ambient and controlled traffic loads. Displacement, strain and integrated acceleration DAFs were computed under different loading conditions. Modal properties were evaluated and used to correlate a three dimensional finite element model for the bridge, including non-linear cable behaviour. The paper discusses the experimental setup as well as the techniques used to evaluate vibration frequencies, mode shapes and the DAF.
Keywords: Dynamic testing; Modal analysis; Suspension bridge; Cable stayed bridge; Dynamic amplification; Numerical correlation